Notes on the princesses daily lives in the kingdom of Navarre (1365-1400) : food, clothing, religion and travel (Estudios de Historia de España, 2017)
The “hostales” —a term used in the ancient kingdom of Navarre to designate royalty homes— are a unique and irreplaceable place that acknowledges everyday life of queens, princes and princesses of the royal family. At a determined age, they possessed their own residence with a special staff responsible for their care and economic management. Expense accounts of these homes were registered in detailed in books or “escroas”. These records provide various elements to make a detailed analysis of proposed topic, in the selected period from 1365 to 1400.Successive coves at unprecedented or precedented document enable us to obtain interesting reports to reconstruct the daily life of the royal residences, visitors, their tastes and pleasures, special meals, clothing ornaments in their sometimes exotic, trips, forms of mercy, celebrations, etc.
Keywords: Hostales; Food; Clothing; Religion; Travel